Unilateral versus Bilateral T3 Ganglionectomy in Primary Palmar Hyperhidrosis Patients - Shih, Beatrice Chia-Hui; Moon, Duk Hwam; Lee, Sungsoo (The Thoracic and Cardiovascular Surgeon, 2025)
Primary palmar hyperhidrosis (PPH) causes excessive hand sweating, impacting daily activities and quality of life. Endoscopic thoracic sympathectomy (ETS), including ganglionectomy, is a common treatment, but the risk of compensatory hyperhidrosis (CH) remains a concern. This study compares unilateral versus bilateral T3 ganglionectomy, focusing on differences in CH occurrence and patient satisfaction.We retrospectively analyzed 118 patients who underwent either unilateral or bilateral T3 ganglionectomy for PPH at our institution from November 2023 to January 2025. Data on patient characteristics and surgical outcomes were extracted from electronic medical records. Patient satisfaction and incidence of CH were assessed at postoperative 3 months.Of the 118 patients with severe PPH, 77 underwent bilateral T3 ganglionectomy, and 41 received unilateral T3 ganglionectomy. No significant differences in baseline characteristics were observed between the groups. Postoperative satisfaction was higher in the unilateral group, with 93% reporting being “very satisfied” compared with 61% in the bilateral group (p < 0.001). The unilateral group also had fewer incidences of CH, with 80% reporting no CH, while 43% of the bilateral group experienced mild CH (p = 0.007). The most common areas affected by CH were the back, thighs, chest, abdomen, and hips. In the unilateral group, 7.5% showed improvement in contralateral sweating, with 22% necessitating contralateral ganglionectomy.This study is the first to compare the effectiveness and incidence of CH between unilateral and bilateral ETS for PPH. Our results show that 93% of unilateral ETS patients reported high satisfaction, compared with 61% in the bilateral group. Eighty percent of the unilateral group experienced no CH, while only 43% in the bilateral group reported mild CH. Statistically significant differences were observed in both satisfaction scores (p < 0.001) and CH occurrence (p = 0.007), suggesting unilateral ETS may provide better symptom relief with fewer adverse effects. Compared with prior studies, our cohort showed improved bilateral ETS outcomes, with only 48% developing CH. These findings indicate that unilateral ETS may be preferred for patients seeking higher satisfaction and reduced risk of CH, though further long-term studies are needed to confirm such results.
Keywords: hyperhidrosis; minimally invasive surgery (includes port access; minithoracotomy); practice guidelines; quality of life